Inclusive Instruction in Elementary Physical Education: A Study of Teachers' Beliefs and Attitudes - Sari, Merlina; Nazirun, Novia; Gazali, Novri; Irma, Ade; Septiani, Desi Yulia; Abdullah, Nagoor Meera (Jp.jok (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan), 2023)
Teachers' beliefs and attitudes about teaching students with disabilities in a physical education setting are the most important factors in inclusive education, as teachers' attitudes directly influence success in learning. This study aimed to assess physical education teachers' beliefs and attitudes regarding teaching students with disabilities in inclusive primary schools. A qualitative approach was used with a sample of 12 physical education teachers from 24 inclusive education-provider schools in Pekanbaru. Data were collected through semi-structured interviews and observation checklists and analysed using content analysis. Findings showed significant variation in teachers' beliefs regarding the potential of students with disabilities in physical education. While some teachers showed a strong belief in the abilities of these students, others remained sceptical. In addition, some teachers were more confident in teaching students with mild disabilities compared to students with more severe disabilities. These findings underline the importance of improving teachers' understanding of the potential of students with disabilities in the context of physical education. This research contributes to a better understanding of physical education teachers' perspectives on inclusive education, which serves as a basis for improving training and support strategies for teachers who face challenges in teaching students with diverse disabilities.